Electronic specific heat of an a3-helical polypeptide and its biochemical variants - Bezerril, Leonardo Mafra (2012)
We perform a theoretical study of the temperature dependent electronic specific heat at constant volume CV ðTÞ for a fibrous a3-helical polypeptide, which has the amino acid sequence (Leu-Glu-Thr-Leu-Ala-Lys- Ala)3, considering only its primary structure. We focus also on two different variants of the a3-helical polypeptide, namely those with (5Qa3 variant, mutation Ala5Gln) and without (7Qa3 variant, mutation Ala7Gln) fibrous assemblies. The energy spectra are calculated using a two-dimensional Schrödinger equation within a tight-binding approximation in which the isolated amino acid vertical ionization energy and the hopping terms are found using density functional theory computations